تأليف الرسائل الفقهية المفردة: أسبابه ومناهجه - Seyed Sivan Seyed Osman Farougi (البصيرة: مجلة الدراسات الإسلامية, 2024)
This type of writing is usually called special fiqh or individual fiqh treatises. In general, these treatises discuss certain issues, or certain branches of the topic of Islamic jurisprudence, with in-depth study and deeper scrutiny, and the author separates them from all other topics of Islamic jurisprudence. This type of fiqh writing generally occurs in all schools of thought, so writings that discuss certain fiqh issues are presented in special sections related to a branch or problem of fiqh according to the diversity of conditions, reasons, and motives. Fiqh treatises that briefly discuss this particular issue have appeared throughout history, and their number is unlimited, although very numerous, but those printed from these treatises compared to their manuscripts are few. Public and private manuscript treasuries are still filled with fiqh treatises such as this. Considering the importance of fiqh treatises in explaining many problems and helping someone explain sharia laws to problems that have recently occurred and require the establishment of sharak laws, it is very important to study these treatises. This research aims to introduce fiqh treatises that discuss certain issues, the reasons for writing them, as well as explaining the authors' methods in basic terms and practice using examples of cases found in schools of fiqh.